STRESSED BREAST CANCER PATIENT - A CASE REPORT - W., Sampoornam (Journal of Health and Allied Sciences NU, 2014)
Breast cancer can cause stress and the patients may need nurse's support for the ventilation of feelings and thoughts. A female patient aged 45 years newly diagnosed with breast cancer was stressed. Patient was made to ventilate feelings through face to face confrontation and observed for one month duration. The patient showed reduction in the stress level.
Keywords: Stress; Breast cancer